Are animals moral?: Zhu Xi and Jeong Yakyong's views on nonhuman animals. Issue 2 (3rd April 2018) - Back, Youngsun
ABSTRACT: One significant feature of Jeong Yakyong's丁若鏞 (1762–1836) thought is his deconstruction of Zhu Xi's 朱熹 (1130–1200) moral universe based on li 理 and qi 氣. For Zhu Xi, the world in its entirety was a moral place, but Jeong Yakyong distinguished nonmoral domains from the moral domain. One question that follows in pursuing a comparison of their philosophies on this topic is what each thinker meant by 'moral' and, in particular, whether they meant the same thing. In this paper, I delve deeper into this topic by comparing their respective perspectives on whether nonhuman animals are moral. Interestingly, they held exactly opposite views: Zhu Xi believed that certain actions on the part of nonhuman animals manifest moral values, whereas Jeong Yakyong claimed that none of the actions of nonhuman animals has moral value. In comparing their views, I introduce Mark Rowlands' distinction between 'moral subjects' and 'moral agents.'